STUDI GAMBARAN PELAKSANAAN PRAKTEK KERJA PROFESI APOTEKER DI APOTEK DI DAERAH ISTIMEWA YOGYAKARTA - Bondan Ardiningtyas; Marchaban Marchaban; Hari Kusnanto; Achmad Fudholi (Jurnal Ilmiah Farmasi, 2017)
Abstract Pharmacy internship in pharmacies is an important stage to prepare prospective pharmacists as health workers. Knowing the process of pharmacy internship implementation is very important in improving the learning system, recognizing obstacles and providing recommendations for solutions to improve the quality of pharmacy education. This aims to know the description of the process and the obstacle of pharmacy internship in pharmacies. The implementation and constraints of the preceptors during pharmacy internship in pharmacies were collected throughFocus Group Discussion (FGD) involving 18 preceptors in Yogyakarta. The data collected were transcribed and categorised, then analysed qualitatively. The Duration, effective hours, process flow, assessment methods still vary, some weresubjective and undocumented; most do not have written procedures and procedures; and evaluation has not been done consistently also has not been acted upon. Constraints include: timing difficulties; compensation; lack of facilities support; limitations on the number and skills of pharmacists and pharmacy employees; as well as the lack of enthusiastic students. The implementation of pharmacy internship in pharmacies needs to be improved to upgrade the competencies of pharmacist graduates. Keywords: preseptors, focus group discussion, pharmacy internship, pharmacies Intisari Praktek Kerja Profesi Apoteker (PKPA) di Apotek merupakan tahap penting untuk mempersiapkan calon apoteker sebagai tenaga kesehatan. Mengetahui proses pelaksanaan PKPA sangat penting dalam memperbaiki sistem pembelajaran, mengenali kendala dan memberikan rekomendasi solusi untuk meningkatkan kualitas pendidikan farmasi. Tujuan penelitian ini adalah untuk mengetahui gambaran pelaksanaan dan kendala preseptor dalam pelaksanaan PKPA di Apotek. Focus Group Discussion (FGD) melibatkan 18 orang preceptor PKPA apotek di Daerah Istimewa Yogyakarta, dilanjutkan dengan analisa kualitatif.  Durasi, jam efektif, alur proses, metode penilaian masih bervariasi; bersifat subyektif dan belum terdokumentasi; sebagian besar belum memiliki tata tertib dan prosedur tertulis; evaluasi belum dilakukan secara konsisten dan belum ditindaklanjuti. Kendala meliputi: kesulitan pengaturan waktu; kompensasi; kurangnya dukungan fasilitas; keterbatasan jumlah dan keterampilan apoteker dan karyawan apotek; serta kurangnya antusias mahasiswa. Pelaksanaan Praktek Kerja Profesi Apoteker di Apotek perlu segera diperbaiki dan ditingkatkan untuk menghasilkan lulusan apoteker yang kompeten. Kata kunci: preseptor, focus group discussion, Praktek Kerja Profesi Apoteker, apotek